To find which expression equals 9000, let's calculate each one:
- \( 10 \times 900 = 9000 \)
- \( 100 \times 900 = 90000 \)
- \( 10 \times 90 = 900 \)
- \( 1000 \times 90 = 90000 \)
Only the first expression, \( 10 \times 900 \), equals 9000.
10 × 900
100 × 900
10 × 90
1000 × 90
3 answers
To find which expression equals 9000, let's calculate each one:
Only the first expression, \( 10 \times 900 \), equals 9000.
Yes, that is correct.
To verify again:
Only \(10 \times 900\) equals 9000. The other expressions do not equal 9000.